Konsep dan Implementasi Pendidikan Karakter dalam Perspektif Al-Qur’an - Rifa'i, Muhammad Rizal (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Character education is a serious effort to understand, form, and foster ethical values. One of the scopes of character education is moral education. In writing this article, the author focuses the study on moral education contained in the verses of the Koran. Based on the study that the author has conducted, there are three themes regarding moral education in the Koran; First, the message to always obey Allah SWT. This message is found in QS. Luqman (31): 13. Second, the message is to always obey your parents. This message is found in QS. Luqman (31): 14. Third, the message is to stay away from arrogance. This message is found in QS. Luqman (31): 18. The implementation of Al-Qur'an-based character education in daily life is very dependent on the role of: 1) family and society through deepening the Prophet's creed and morals, as well as familiarizing them with the norms of daily life. 2) the world of education through lesson curricula, school facilities and mosques. The research approach uses a qualitative approach through library research with data sources from the Al-Qur'an as well as several tafsir books from several experts on Al-Qur'an exegesis related to The research topic is character education in the Qur'an, as well as several experts' views on character education.